2018
DOI: 10.1093/ehjci/jey171
|View full text |Cite
|
Sign up to set email alerts
|

Left atrial function in heart failure with mid-range ejection fraction differs from that of heart failure with preserved ejection fraction: a 2D speckle-tracking echocardiographic study

Abstract: Aims Heart failure (HF) with mid-range ejection fraction (HFmrEF) shares similar diagnostic criteria to HF with preserved ejection fraction (HFpEF). Whether left atrial (LA) function differs between HFmrEF and HFpEF is unknown. We, therefore, used 2D-speckle-tracking echocardiography (2D-STE) to assess LA phasic function in patients with HFpEF and HFmrEF. Methods and results Consecutive outpatients diagnosed with HF according to current European recommendations were prospectively enrolled. There were 110 HFp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
18
2
4

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(33 citation statements)
references
References 38 publications
8
18
2
4
Order By: Relevance
“…With senescence, LA contraction augments as a compensatory mechanism with a late decrease with further aging . The same changes are reported with LV diastolic dysfunction . In early stages, LA reservoir and conduit strain decreases and an increase in its booster function can compensate filling.…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…With senescence, LA contraction augments as a compensatory mechanism with a late decrease with further aging . The same changes are reported with LV diastolic dysfunction . In early stages, LA reservoir and conduit strain decreases and an increase in its booster function can compensate filling.…”
Section: Discussionsupporting
confidence: 52%
“…21 The same changes are reported with LV diastolic dysfunction. 22,23 In early stages, LA reservoir and conduit strain decreases and an increase in its booster function can compensate filling. But with prolonged dysfunction, LA dilation occurs, and eventually, LA mechanical function shows a fall in the relative contribution of LA pump to LV filling.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with recent reports, we observed a marked reduction in left atrial reservoir strain in HFpEF compared to reference controls. 18,20,21,34 In contrast to our original hypothesis;…”
Section: Discussioncontrasting
confidence: 79%
“…[9][10][11][12][13][14][15][16][17] To the best of our knowledge, no study has evaluated left atrial function in women with INOCA. Given that left atrial function is often impaired in HFpEF, 16,[18][19][20][21] we hypothesized that left atrial function would also be impaired in INOCA. pressure (LVEDP or pulmonary capillary wedge pressure at rest >15 mmHg and/or with exercise ≥25 mmHg, b-type natriuretic peptide >100 pg/mL, or current use of diuretic).…”
Section: Introductionmentioning
confidence: 99%
“…In HFrEF, the contractile atrial functions were found to be lower compared with HFpEF patients (9). Additionally, in HFrEF patients, along with the reduced LA reservoir function, there was a reduction in RV systolic function and an increase in pulmonary pressure (10).…”
Section: Introductionmentioning
confidence: 93%